EduSdamada: Developing an Educational Mobile Game for Elementary School Children using Unity2D: EduSdamada: Pengembangan Game Edukasi untuk Anak Sekolah Dasar dengan Menggunakan Unity2D - Prasetio, Aga Dandi; Rosid, Mochamad Alfan (Indonesian Journal of Innovation Studies, 2023)
This research focuses on the development of an educational mobile game, 'EduSdamada,' using the Unity2D application, with the aim of addressing the impact of information technology on education. As mobile phones and smartphones greatly influence learning, teachers are challenged to adopt effective methods to engage students. The game combines learning and play elements to provide enjoyable and effective learning experiences for elementary school children. The research follows the ADDIE model (analysis, design, development, implementation, and evaluation) commonly used for software and application development. Data collected through questionnaires from 7-year-old children revealed that 81.8% of them enjoy playing games that incorporate learning aspects, and 45.5% found 'EduSdamada' to be an enjoyable experience. While the game exhibits some shortcomings in terms of graphics, features, and effects, the findings underscore the potential for future improvements. Highlights: Developed an educational mobile game, 'EduSdamada,' using Unity2D application, catering to the impact of information technology on education. The game successfully combines learning and play elements, providing enjoyable and effective learning experiences for elementary school children. Data analysis from questionnaires revealed that 81.8% of 7-year-old children enjoy playing games with educational components, with 45.5% finding 'EduSdamada' to be an enjoyable experience, indicating its potential for further improvements.